2008
DOI: 10.1007/s00415-008-0665-5
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of olfactory function in patients with idiopathic Parkinson's disease

Abstract: Olfactory function is diminished in patients with idiopathic Parkinson disease (IPD). Because previous work almost exclusively relied upon cross-sectional studies, the present investigation aimed to address the correlation between olfactory loss and duration of disease within the context of a longitudinal study, accompanying well-diagnosed patients over an average period of 4.4 years. A group of 27 IPD patients was examined (5 women, 22 men; age range 27-64 years; duration of disease: 0 to 19 years). Psychophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 24 publications
2
66
0
6
Order By: Relevance
“…[6,7]. One longitudinal study found conflicting results as to whether olfaction worsened over time [8].…”
Section: Parkinson's Disease (Pd) Is a Neurodegenerative Disorder Of mentioning
confidence: 99%
“…[6,7]. One longitudinal study found conflicting results as to whether olfaction worsened over time [8].…”
Section: Parkinson's Disease (Pd) Is a Neurodegenerative Disorder Of mentioning
confidence: 99%
“…6 The high prevalence of olfactory dysfunction in patients with IPD suggests that IPD may actually be an olfactory disease. 5,6 Recent neuropathologic advances suggest that the olfactory system is among the earliest brain regions involved in PD 7 and olfactory deficits are associated with the presence of incidental Lewy bodies in the brains of decedents without parkinsonism or dementia during life. 8 Results from postmortem studies revealed Lewy bodies in the OB 9 but also in other brain regions related to olfaction, such as the anterior olfactory nucleus, 10 the piriform cortex, 11 the amygdaloid complex, 12 the entorhinal cortex, and the hippocampal formation.…”
mentioning
confidence: 99%
“…[1][2][3] Between 70% and 90% of patients with PD have olfactory deficits independent of disease severity and duration. 4,5 Olfactory dysfunction is thus the second most common feature of this disorder, following rigidity and akinesia. 6 The high prevalence of olfactory dysfunction in patients with IPD suggests that IPD may actually be an olfactory disease.…”
mentioning
confidence: 99%
“…(Kaufmann H et al, 2004;Goldstein D et al, 2010). Once IPD has become clinically manifest, olfaction appears to be already severely compromised, which is in line with the absence of longitudinal changes of olfactory function during IPD progression (Herting et al 2008). In a recent study (Wattendorf E et al, 2009) gray matter atrophy was investigated using morphometric analysis of magnetic resonance images voxel-based morphometry (VBM) and it was related to psychophysically measured scores of olfactory function in early PD patients, moderately advanced PD patients and age-matched healthy controls.…”
Section: Wwwintechopencommentioning
confidence: 87%